What are the relative macroeconomic merits and environmental impacts of direct job creation and basic income guarantees? - Pavlina R. Tcherneva (Levy Economics Institute of Bard College, 2007)
There is a body of literature that favors universal and unconditional public assurance policies over those that are targeted and means-tested. Two such proposalsthe basic income proposal and job guaranteesare discussed here. The paper evaluates the impact of each program on macroeconomic stability, arguing that direct job creation has inherent stabilization features that are lacking in the basic income proposal. A discussion of modern finance and labor market dynamics renders the latter proposal inherently inflationary, and potentially stagflationary. After studying the macroeconomic viability of each program, the paper elaborates on their environmental merits. It is argued that the green consequences of the basic income proposal are likely to emerge, not from its modus operandi, but from the tax schemes that have been advanced for its financing. By contrast, the job guarantee proposal can serve as an institutional vehicle for achieving various environmental goals by explicitly targeting environmental rehabilitation, conservation, and sustainability. Finally, in the hope of consensus building, the paper advances a joint policy proposal that is economically viable, environmentally friendly, and socially just.
Keywords: E42; E61; H23; J68; Q58; 330; Macroeconomic Stability; Inflation; Unemployment; the Environment; Employer of Last Resort; Basic Income Guarantee